Conference on Lasers and Electro-Optics 2018
DOI: 10.1364/cleo_at.2018.jtu2a.29
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced performance of 450 nm GaN laser diodes with an optical feedback for high bit-rate visible light communication

Abstract: Enhanced performance of 450 nm GaN laser diodes with an optical feedback for high bit-rate visible light communication. Conference on Lasers and Electro-Optics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…These trend of optical injection dynamics are similar to that of the injection locked laser diodes reported in the literature [23], and suggests consistency in our measurements and further affirming our attribution of EOI as a signature of EIL. Moreover, Figure 5 also indicates another possible further transition into an unstable region for > 0.7 dB (blue) and > 1.3 dB (red), with inferior performance, as observed in literature [23][24][25]. On the whole, comparing the results of SIL and EOI, we found that the linewidth of blue (red) laser exhibited ~< 80 (~90) pm value under selfinjection and ~78(~100) pm value under external-injection, and at a fixed IR of -0.7 dB and -1.25 dB, respectively.…”
Section: External Optical Injection Characterizationsupporting
confidence: 73%
See 2 more Smart Citations
“…These trend of optical injection dynamics are similar to that of the injection locked laser diodes reported in the literature [23], and suggests consistency in our measurements and further affirming our attribution of EOI as a signature of EIL. Moreover, Figure 5 also indicates another possible further transition into an unstable region for > 0.7 dB (blue) and > 1.3 dB (red), with inferior performance, as observed in literature [23][24][25]. On the whole, comparing the results of SIL and EOI, we found that the linewidth of blue (red) laser exhibited ~< 80 (~90) pm value under selfinjection and ~78(~100) pm value under external-injection, and at a fixed IR of -0.7 dB and -1.25 dB, respectively.…”
Section: External Optical Injection Characterizationsupporting
confidence: 73%
“…Besides, a clear eye diagram at 2.0 Gb/s of the SIL and the FR laser diodes, shown in the insets of Figures 8 (a) and (b), displays an error-free transmission. The authors' strongly believes that the limitation of APD bandwidth possibly have restricted observation of further improvement from the SIL system and attributed this slight improvement in part to a slight increase in the integrated power of the system, and partly to reduced system noise, under SIL, which has been observed previously [24]. A clear distinction in the transmission performance should be possible if phase modulation schemes were to be employed, as it is well known that injection locking substantially reduces the intensity as well as phase noise of the SIL laser system.…”
Section: Ook-nrz Transmission Employing a Sil Blue And Red Laser Diodementioning
confidence: 70%
See 1 more Smart Citation
“…In summary, a maximum bandwidth enhancement of ∼880 MHz (1.53-2.41 GHz) for green, ∼540 MHz (1.72-2.26 GHz) for the blue and ∼320 MHz (1.92-2.24 GHz) for the red laser diodes are achieved via self-injection locking technique. It is worth mentioning at this instance that all these lasers exhibited significant performance improvement compared to our first and initial results on spectral linewidth (∼1.3 times) and modulation bandwidth (∼2 times) improvement, which were reported on an unoptimized setup [16], [17].…”
Section: Effect Of Optical Power Injection Ratiomentioning
confidence: 49%
“…Very recently, owing to the merits offered by SIL viz. energy efficiency, compact scheme, etc., our group successfully demonstrated SIL on 524 nm green [16] and 450 nm blue InGaN/GaN diode lasers [17]. Besides, [18] utilized SIL to demonstrate a single longitudinal mode operation at 446.5 nm blue laser diode with magnesium fluoride (MgF 2 ) whispering gallery mode (WGM) resonator.…”
Section: Introductionmentioning
confidence: 99%